Foreign Direct Investments and Gross Domestic Product Development in USA, European Union and China (1995-2014) - Soleimani, Daryoush; Maitah, Mansoor; Malec, Karel; KotÃ¡skovÃ¡, Sylvie Kobzev (International Journal of Economics and Financial Issues, 2016)
EU and China established diplomatic relations in 1975, and now became mutually indispensable economic partners, presenting both an opportunity and challenge. During that time, after the first market reforms which were introduced in 1978, China has transitioned from a predominantly agricultural to industrial and service-oriented economy. On 11 December 2001, China also became the 143rd member of the WTO. The aim of this research is to quantitatively compare the US, EU and Chinese GDP from 1995 to 2014, the US and Chinese outward FDI from 1995 to 2013, and analyse the impact of the exponentially rising Chinese investments in the European Union (EU). We have found that while the US economy experienced a regression in general, and exhibited outward FDI exponential decrease in particular, the Chinese outward FDI sustained an exponential growth. There is also possible to expect continue of exponentially rising economic investment of China in the EU. The Chinese investment in the EU is estimated to peak during the next decade, when China will become by far the foremost economic partner of the EU. Keywords: China, European Union, United States GDP, Foreign Direct Investment JEL Classifications: F5, F4, O51, O52, O53